Performance implications of industry appropriability for manufacturing SMEs: The role of technology orientation. Issue 5 (1st June 2015) - Batra, Safal; Sharma, Sunil; Dixit, Mukund R; Vohra, Neharika; Gupta, Vishal K
Abstract : Purpose: – Industry appropriability – the degree to which firms in an industry can appropriate benefits from their innovations – is a crucial dimension of industry environment. Small and medium manufacturing enterprises (manufacturing SMEs), because of their limited resource base, tend to be especially sensitive to the appropriability conditions in their industry. The purpose of this paper is to understand the influence of industry appropriability on firm outcomes (innovativeness and performance), and posits technology orientation as a dynamic capability that helps firms overcome appropriability barriers in their industry. Design/methodology/approach: – Data were collected from 162 manufacturing SMEs in India. Multiple linear regression analysis was used to test the proposed hypotheses. Findings: – This study reveals that the perceived level of appropriability of manufacturing SMEs impacts their innovativeness. Further, findings also support technology orientation as a crucial firm-specific characteristic which enables firms to overcome unfavorable appropriability conditions. Technology orientation plays a significant role in mitigating the negative impact of lower appropriability conditions. Even when the patent regime is unfavorable, technology-oriented firms are able to innovate and perform better. Practical implications: – The findings suggest technology orientation as a strategic mechanism for manufacturing SMEs to respond to conditions of unfavorable appropriability regime. Originality/value: – This study elaborates the benefits of integrating industry-level and firm-level characteristics. Specifically, an attempt was made to extend the existing research on industry appropriability by bringing in the contingent effect of technology orientation. The context of manufacturing SMEs yielded several interesting insights.